Basic science concepts and applications for wastewater. (American Water Works Association, 2003)
Annotation Wastewater operators will find practical discussions of mathematics, hydraulics, chemistry, and electricity as they relate to wastewater topics and system operations. Includes a glossary and index, as well as appendices incorporating conversion tables, the periodic table, a list of elements, and color plates.
Keywords: Sewage -- Purification.; Science.; elektronické knihy; electronic books